Leaf shredding as an alternative strategy for managing apple scab resistance to demethylation inhibitor fungicides - Meitz-Hopkins, Julia C.; von Diest, Saskia G.; Koopman, Trevor A.; Tobutt, Kenneth R.; Xu, Xiangming; Lennox, Cheryl L. (Frontiers in Horticulture, 2023)
Within integrated apple scab control there is a strong focus on reduction of Venturia inaequalis primary inoculum. The hypothesis that leaf shredding as an orchard sanitation practice would reduce the effective population size of the fungus (resulting in lower genetic variation due to reduction in sexual offspring) was tested. Assuming the allele causing fungicide resistance is already present in the population, it will be widely distributed at the end of the season, since selection occurs when the demethylation inhibitor (DMI) fungicide was applied. For short-term disease management a reduction of inoculum size, (i.e. potential ascospore dose) is most important. In the long-term resistant isolates/genotypes would be less likely to survive the winter and/or to infect in the spring, if that inoculum (i.e. in fallen leaves) has been removed. To sustain the use of highly effective synthetic fungicides, such as the DMIs, fungicide resistance management practices have to be evaluated. This study quantified the effect of leaf shredding on changes in the pathogen's flusilazole sensitivity and population genetic structure. Fungicide resistance, which negatively affects pathogen fitness, is hypothetically reversible, if the selection pressure by the fungicide is removed. Therefore V. inaequalis populations in orchard trials, where sanitation practices had been applied, were tested for flusilazole sensitivity in planta and in vitro. Significant shifts towards flusilazole resistance were identified in orchards with a history of DMI application without sanitation treatment, with a mean sensitivity of EC50= 0.208 ug/ml (n=49) compared to an unexposed V. inaequalis population (EC50= 0.104 ug/ml, n=55). However, the isolates from the same sanitation trial orchards, from leaf shredding treatment in combination with a fungicide spray programme, had a mean EC50 of 0.110 ug/ml (n=41), similar to an unexposed V. inaequalis population. Furthermore, V. inaequalis offspring after sanitation In preparation for Frontiers in Horticulture treatment, showed shifts in microsatellite allele frequency distribution patterns used as an indicator of sexual reproduction. This study concludes that sanitation treatments, i.e. leaf shredding, impact on fungicide sensitivity and therefore effectively contributes to fungicide resistance management.